PENYULUHAN KONTRASEPSI GUNA MENINGKATKAN PENGETAHUAN KESEHATAN REPRODUKSI PASANGAN USIA SUBUR DI PUSKESMAS WAY PANJI LAMPUNG SELATAN TAHUN 2017 - Rilyani Rilyani; Prima Dian Furqoni; Triyoso Triyoso; Patrur Korip (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACTIndonesia in 2013 amounted to 248.4 million people. The government's policy in overcoming this is by establishing Family Planning (KB) program as government program since 1970 together with National Family Planning Coordinating Agency with the aim to suppress the growth of population and improve reproductive health status . The target of the Family Planning Program is divided into 2, namely the direct and indirect goals.  The objectives is to increase knowledge of fertile couples of Way Panji, South Lampung about reproductive health and birth control program by contraception. This activity was done on Monday, December 25, 2017 UPT Puskesmas way Panji South Lampung with the number of participants 19 people. The result of this avtivity expected that the community can manage the number of children and the time of birth so can reduce risks to mothers, then create a healthier and better family. Keywords: Contraception, Birth, Reproduction